2021
DOI: 10.3390/polym13162677
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Interlayer Bond Strength during Fused Filament Fabrication of Nylon Copolymers: An Interplay between Thermal History and Crystalline Morphology

Abstract: One of the main drawbacks of Fused Filament Fabrication is the often-inadequate mechanical performance of printed parts due to a lack of sufficient interlayer bonding between successively deposited layers. The phenomenon of interlayer bonding becomes especially complex for semi-crystalline polymers, as, besides the extremely non-isothermal temperature history experienced by the extruded layers, the ongoing crystallization process will greatly complicate its analysis. This work attempts to elucidate a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…This may be indicative of the unsuitability of the crazing model to properly describe the failure of PLA welds with frozen-in orientation. Another possible reason is the existence of a low degree of crystallinity at the weld, which could effectively decrease the strength of the inter-layer bonding [ 31 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be indicative of the unsuitability of the crazing model to properly describe the failure of PLA welds with frozen-in orientation. Another possible reason is the existence of a low degree of crystallinity at the weld, which could effectively decrease the strength of the inter-layer bonding [ 31 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, in the study of poly-ether-ether-ketone (PEEK) printed samples, Xu et al showed that a reduction of molecular mass can increase fluidity, reduce internal defects and, consequently, significantly improve the mechanical properties of the printed product [ 30 ]. Moreover, by employing a trouser tear test, Vaes et al demonstrated that for nylon copolymers a decrease of the feedstock molar mass improved interlayer adhesion, due to the increased equivalent weld time [ 31 ]. However, the possible effect of residual orientation at the weld interface was neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the semi-crystalline nature of these co-polyester materials, the high-frequency and low temperature rheology data is inaccessible via traditional techniques. Thus, here we extrapolate to low temperatures via the WLF equation to calculate weld time, as is done broadly in the field [21,34]. We note that the WLF equation is known to be inaccurate in the vicinity of the glass transition temperature (e.g., see Ref [35,36]), thus here we report a qualitative comparison of the materials rather than an accurate prediction of the weld times; by comparing the two materials at the same print bed temperature the weld time of HT is limited compared to NGEN.…”
Section: Rheological Characterizationmentioning
confidence: 99%
“…It is expected that a chamber temperature above Tg could trigger the DA bonds formation between colliding particles, thus affecting the powder flow properties and particle size distribution for further reusage [48]. Regular amorphous and semicrystalline thermoplastics used in additive manufacturing commonly exhibit a weak interlayer bonding in the printing z-direction due to the hindered interlayer chain diffusion upon cooling [59].…”
Section: Selective Laser Sintering Parametersmentioning
confidence: 99%